Associations between fruit and vegetable consumption and depressive symptoms: evidence from a national Canadian longitudinal survey. Issue 2 (26th August 2015) - Kingsbury, Mila; Dupuis, Gabrielle; Jacka, Felice; Roy-Gagnon, Marie-Hélène; McMartin, Seanna E; Colman, Ian
Abstract : Background: Several cross-sectional studies have demonstrated associations between diet quality, including fruit and vegetable consumption, and mental health. However, research examining these associations longitudinally, while accounting for related lifestyle factors (eg, smoking, physical activity) is scarce. Methods: This study used data from the National Population Health Survey (NPHS), a large, national longitudinal survey of Canadians. The sample included 8353 participants aged 18 and older. Every 2 years from 2002/2003 to 2010/2011, participants completed self-reports of daily fruit and vegetable consumption, physical activity, smoking and symptoms of depression and psychological distress. Using generalised estimating equations, we modelled the associations between fruit and vegetable consumption at each timepoint and depression at the next timepoint, adjusting for relevant covariates. Results: Fruit and vegetable consumption at each cycle was inversely associated with next-cycle depression (β=−0.03, 95% CI −0.05 to −0.01, p<0.01) and psychological distress (β=−0.03, 95% CI −0.05 to −0.02, p<0.0001). However, once models were adjusted for other health-related factors, these associations were attenuated (β=−0.01, 95% CI −0.04 to 0.02, p=0.55; β=−0.00, 95% CI −0.03 to 0.02, p=0.78 for models predicting depression and distress, respectively). Conclusions: These findings suggest that relations between fruit and vegetable intake, other health-related behaviours and depression are complex. Behaviours such as smoking and physical activity may have a more important impact on depression than fruit and vegetable intake. Randomised control trials of diet are necessary to disentangle the effects of multiple health behaviours on mental health.